2014
DOI: 10.1021/nn500064s
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Device Applications for Semiconducting Two-Dimensional Transition Metal Dichalcogenides

Abstract: With advances in exfoliation and synthetic techniques, atomically thin films of semiconducting transition metal dichalcogenides have recently been isolated and characterized. Their two-dimensional structure, coupled with a direct band gap in the visible portion of the electromagnetic spectrum, suggests suitability for digital electronics and optoelectronics. Toward that end, several classes of high-performance devices have been reported along with significant progress in understanding their physical properties… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
1,845
2
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 2,486 publications
(1,924 citation statements)
references
References 230 publications
17
1,845
2
10
Order By: Relevance
“…One‐ or few‐atom‐thick 2D layered materials (2DLMs), formed by lateral covalent bonds and vertical van der Waals (vdWs) forces, exhibit extraordinary electronic and optical properties1, 2, 3, 4, 5 and are therefore considered building blocks of next‐generation electronic devices. Recently, considerable research interest has been intrigued by the vertically stacked vdWs integration of various 2DLMs, which provides infinite possibilities by overcoming the limitation of lattice matching and processing compatibility 6, 7, 8, 9, 10, 11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…One‐ or few‐atom‐thick 2D layered materials (2DLMs), formed by lateral covalent bonds and vertical van der Waals (vdWs) forces, exhibit extraordinary electronic and optical properties1, 2, 3, 4, 5 and are therefore considered building blocks of next‐generation electronic devices. Recently, considerable research interest has been intrigued by the vertically stacked vdWs integration of various 2DLMs, which provides infinite possibilities by overcoming the limitation of lattice matching and processing compatibility 6, 7, 8, 9, 10, 11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Many TMDs possess al ayered structure akin to graphite, and within one layer of TMDs,t he transition metal is sandwiched between two chalcogens, hence resulting in the MX 2 stoichiometry.I th as been reported that the bonds within each layer are covalent, whereas the bonds between two different MX 2 layersa re typicallyh eld by van der Waals forces of interactions, thus allowing exfoliation of TMDs down to single layers. [9,[13][14][15][17][18][19] The unique and advantageous properties of TMDs,s uch as large surface area,t uneable band gaps, stability against photocorrosion,a nd low shear resistance due to weak van der Waals interactions between layers have attracted much research attention and led to numerous and diversified applications of TMDs. [13,14,20,21] Such applicationsi nclude electrocatalytic hydrogen evolution, high performance electrochemical supercapacitors, biosensors, field-effect transistors (FETs), photodetectors, heterostructure junctions, photovoltaics, and lubricant additives.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] TMDs have ag eneral chemical formula of MX 2 ,w hereby M represents at ransition metal (for instance Ti,V ,N b, Ta,M o, W, and so on) of a + 4o xidation state and Xi sachalcogen (S, Se, or Te)w ith a À2o xidation state . [9,13,14] Different permutations of thesee lements give rise to approximately6 0d ifferent TMDs, where two-thirds of these compounds are reported to assumel ayereds tructures. Generally,t ransition metals from Groups4 -7 generate compounds that are predominantly layered while some Group 8-10 transition metals give rise to three-dimensional crystal compounds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations